2021
DOI: 10.3389/fpsyt.2021.634464
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity Mediates Associations Between Problematic Internet Use, Anxiety, and Depressive Symptoms in Students: A Cross-Sectional COVID-19 Study

Abstract: Background: Problematic internet use (PIU) is a serious global mental health issue that especially manifested during the Coronavirus disease (COVID-19) pandemic. Engagement in PIU as an impulsive coping with mental distress may pose a long-lasting threat to develop anxiety and depressive disorders. The first aim of our study was to investigate the prevalence of PIU and mental distress symptoms during the COVID-19 pandemic among university students in Lithuania. The second aim was to test the hypothesis that PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 74 publications
2
42
0
2
Order By: Relevance
“…The effect size of these results varied from small in the case of anxiety, sleep quality, and well-being indices to medium in the case of depression symptoms. A recent study conducted in Lithuania in the general student population showed significant associations between PIU (as measured by the PIUQ-9 questionnaire), anxiety, and depressive symptoms (Gecaite-Stonciene et al, 2021). Similarly, symptoms of anxiety, depression, and sleep disturbances were associated with PIU among the medical population in studies conducted in other countries (Capetillo-Ventura and Juárez-Treviño, 2015;Younes et al, 2016;Grover et al, 2019;Shadzi et al, 2020).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The effect size of these results varied from small in the case of anxiety, sleep quality, and well-being indices to medium in the case of depression symptoms. A recent study conducted in Lithuania in the general student population showed significant associations between PIU (as measured by the PIUQ-9 questionnaire), anxiety, and depressive symptoms (Gecaite-Stonciene et al, 2021). Similarly, symptoms of anxiety, depression, and sleep disturbances were associated with PIU among the medical population in studies conducted in other countries (Capetillo-Ventura and Juárez-Treviño, 2015;Younes et al, 2016;Grover et al, 2019;Shadzi et al, 2020).…”
Section: Discussionmentioning
confidence: 86%
“…The study results suggest a relationship between a higher CIUS total score and lower subjective sleep quality. Kalmbach et al (2017) suggest that sleep deprivation among physiciansin-training leads to higher medical error rates and may also have a negative effect on the mental health of doctors (Gecaite-Stonciene et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pre-pandemic contexts, multiple studies reported a robust relationship between affect (in particular, negative affect and emotion dysregulation), impulsivity (especially, negative urgency), and an increased risk for problematic internet use (MacLaren et al, 2011;Ostinelli et al, 2021;Velotti et al, 2021). Preliminary data from studies conducted during the COVID-19 pandemic also showed significant relationships between emotional symptoms (anxiety, stress, and/or depression), impulsivity, and heightened internet use (Albertella et al, 2021;Boursier et al, 2020Boursier et al, , 2021Gecaite-Stonciene et al, 2021;Giardina et al, 2021;Sharman et al, 2021;Teng et al, 2021). These studies suggest that exacerbated emotional problems derived from the pandemic and prolonged isolation, along with a certain predisposition to act rashly when facing negative emotional states, may increase the risk for problematic internet use.…”
Section: The Present Studymentioning
confidence: 99%
“…A meta-analysis showed that approximately one-third of college or university students had depressive or anxiety symptoms ( 9 ). Different testing procedures, dates, scales, or the cutoff points of scales may result in varied prevalence rates ( 9 ), such as 12% in Greece ( N = 1,104) ( 10 ) and nearly half in France ( N = 619) ( 11 ). An online survey conducted among 11,787 Chinese college students in February 2020 showed that the prevalence rates of depressive [the Patient Health Questionnaire—nine-item (PHQ-9) ≥ 5] and anxiety [the seven-item Generalized Anxiety Disorder Scale (GAD-7) ≥ 5] symptoms were 25.9 and 17.8%, respectively ( 12 ).…”
Section: Introductionmentioning
confidence: 99%